2021
DOI: 10.1103/physrevd.104.075036
|View full text |Cite
|
Sign up to set email alerts
|

Collider prospects for the muon g2 in a general two-Higgs-doublet model

Abstract: Recent progress on muon g − 2 measurement prompts one to take it even more seriously. In the general two Higgs doublet model that allows extra Yukawa couplings, we take a simplified approach of single enhanced coupling. We fix the charged lepton flavor violating coupling, ρτµ = ρµτ , via the one-loop mechanism, for illustrative masses of the heavy scalar H and pseudoscalar A, where we assume mA = m H + . Since extra top Yukawa couplings are plausibly the largest, we turn on ρtt and find that LHC search for gg … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…As shown in ref. [38], to explain eq. of B(h → τ µ) < 0.15% [55], which constrains |ρ τ µ c γ | < 0.1λ τ for ρ τ µ = ρ µτ .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in ref. [38], to explain eq. of B(h → τ µ) < 0.15% [55], which constrains |ρ τ µ c γ | < 0.1λ τ for ρ τ µ = ρ µτ .…”
Section: Discussionmentioning
confidence: 99%
“…To comply with the Belle bound of B(τ → µγ) < 4.2 × 10 −8 [56], large ρ τ µ means small ρ tt . Even more surprising [38] is that the collider search for gg → H, A → τ µ provides a much better constraint. Combining both flavor and LHC constraints, ρ tt seems limited to small values ρ tt 0.1, which is small compared with λ t ∼ = 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Type-X [18][19][20][21][22][23][24][25][26][27][28][29][30][31] and Flavour-Aligned [32][33][34][35][36][37] versions of the THDM the contributions from two-loop diagrams are dominant in most of the parameter space thanks to mechanisms also available in the GTHDM. Additionally, with LFV, the one-loop diagrams can receive a chirality flip enhancement from including the tau lepton in the diagram loop, as was investigated by [38][39][40][41][43][44][45][46], however they only examined muon g − 2 contributions at the one-loop level.…”
Section: Leptonic Observablesmentioning
confidence: 99%
“…The tighter theoretical constraints come from perturbativity which requires ξ f ij ≤ √ 4π ∼ 3.5. On the phenomenological side, the studies in [43,131] have found values as large as ξ u tt ∼ 0.1 and ξ u tc ∼ 0.32 for masses of the heavy Higgses of order 500 GeV. With respect to the ξ u cc coupling, it has been shown in [132] that O(1) values are possible within the charged anomalies, and similar values were considered in [70] in the context of the neutral anomalies, not only for ξ u cc but for all the Yukawa matrix elements.…”
Section: Parameter Spacementioning
confidence: 99%